DEVELOPING SCREAMBLE MEDIA TO ENHANCE SPEAKING SKILL FOR PRESCHOOLERS - Rosita Aryani (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2019)
This study aims to develop SCREAMBLE media to enhance speaking skill among preschoolers in Cahaya Bangsa School Metro. A research question is formulated: is SCREAMBLE media effective to enhance speaking skill? The participants are 18 preschoolers of Kindergarten B chosen by purposive cluster sampling. This is a kind of educational research and development designed by certain procedures; setting the instructional goals, procedures, and materials, conducting performance objectives, field-testing, assessing instruments, doing formulative and summative evaluation. The result gathered by Wilcoxon test represents Asymp.Sig (2-tailed) values 0,000 which is smaller than 0,05 indicates that SCREAMBLE media is effective to enhance speaking skill. Besides, observation reveals that preschoolers are excited to speak since their fine motor and cognitive aspects are included simultaneously.